Migraine is associated with a higher risk of ischemic and hemorrhagic stroke: an analysis of the All of Us database - Seah, Nick; Chong, Catherine D.; Dumitrascu, Oana M.; Schwedt, Todd J.; Cao, Zhichao; Wu, Teresa (Frontiers in Pain Research, 2025)
BackgroundWhile prior studies suggest an increased risk of stroke among individuals with migraine, particularly those with migraine with aura, data on how specific migraine characteristics and comorbidities influence this risk across diverse populations remain limited. The All of Us database provides a unique opportunity to address this gap given its large sample size and inclusion of historically underrepresented groups.MethodsA cross-sectional case-control analysis using multivariable regression models accounting for vascular risk factors and comorbidities was performed to compare the risk of stroke between individuals with and without migraine, odds ratios (OR) using a 95% confidence interval (CI) were calculated.ResultsWithin the All of Us database, 31,444 individuals received a migraine diagnosis [female = 25,374/81%, male = 5,391/17%, other = 679/2%; mean (std) age = 54.9 (15.6)] and 379,283 did not have a migraine diagnosis [female = 222,104/59%, male = 149,182/39%, other = 7,997/2%; mean (SD) age = 55.9 (17.2)]. The migraine group had a greater proportion of women (81% vs. 59%), a higher proportion of white individuals (61% vs. 55%) and fewer African American individuals (15% vs. 19%). Compared to the non-migraine group, individuals with migraine had higher rates of comorbidities, including depression (46% vs. 12%), diabetes (16% vs. 7%), tobacco use (36% vs. 15%), hyperlipidemia (52% vs. 24%), hypertension (54% vs. 26%), and atrial fibrillation (3% vs. 2%).A multivariable regression model adjusted for differences between group demographics and comorbidities found that compared to those without migraine, individuals with migraine had a higher risk of overall stroke [OR 1.97, 95% CI (1.88, 2.07)], ischemic stroke [OR 1.38, 95% CI (1.24, 1.53)] and hemorrhagic stroke [OR 1.75, 95% CI (1.60, 1.92)]. Individuals with chronic migraine had a higher risk of overall stroke compared to the non-migraine group [OR 2.56, 95% CI ( 2.32, 2.84)] and compared to episodic migraine [OR 1.90, 95% CI (1.81, 2.00)]. Those with migraine with aura had a higher risk of stroke compared to individuals with migraine without aura [OR 1.33, 95% CI (1.20, 1.48)].ConclusionsIndividuals with migraine, particularly those with chronic migraine had a higher risk of stroke compared to those without migraine and compared to individuals with episodic migraine. The risk of stroke was higher in those with migraine with aura compared to those with migraine without aura even after adjusting for vascular comorbidities. Our analysis, using data from the All of Us database, confirms previous findings and suggests that while vascular comorbidities are more prevalent in those with migraine, they do not fully account for the increased risk of stroke.